Islam dan Ilmu Pengetahuan Dalam Diskursus Muslim Kontemporer - M. Zainal Abidin (Ulumuna, 2006)
This paper tries to describe the debate on Islam and knowledge in contemporary Moslem thought regarding with two essential issues. Firstly, how to overcome the decline of knowledge in the Moslem society, secondly, how to deal with knowledge produced by Western civilization. Moslem intellectual response differently on the issues, especially in looking at the character of modern knowledge. Some perceive the knowledge as neutral and universal, so if the Moslem wants to take the knowledge, they have to follow the Western knowledge thoroughly. While the others argue that the knowledge is not neutral. It always depends on its maker, so the Moslem must be aware of Western knowledge. Above all, the contemporary of Moslem scholars realize that the only way to the second resurgence to get the golden age of Islam is through mastering the knowledge for the supremacy of knowledge is the main indicator of the supremacy of a civilization.